META, GOOGLE, TIKTOK VA UNUTILISH HUQUQI: XUSUSIY KORPORATSIYALAR SHAXS DAXLSIZLIGINING KALITIMI? - Saparbayeva Maftuna Ikrom qizi, (TADQIQOTLAR, 2026)
This article analyzes the relationship between the circulation of personal data on Meta, Google, and TikTok platforms and the practical enforcement of the right to be forgotten.  The  study  draws  on  normative-legal  and  comparative  approaches.  The findings  demonstrate  that  platform  design,  indexation  mechanisms,  and  content replication significantly constrain the effective realization of the right to erasure. The scientific contribution lies in clarifying the criteria for corporate governance in the context of personal data protection.